Rekacipta Antarmuka Pengguna Intuitif dan Ramah Pengguna untuk Sistem Operasi Windows: Pendekatan Berbasis Pengalaman Pengguna (Ux) - Rakhmadi Rahman; Abdul Khalik Hartono; Natasya taslim (Jurnal Penelitian Teknologi Informasi dan Sains, 2024)
The rapid development of digital technology has led to the importance of intuitive and user-friendly operating systems. Windows, as one of the most widely used operating systems in the world, therefore we continue to strive to present a user interface (UI) that is not only functional but also easy to use. This journal discusses the project "Recreating Intuitive and User-Friendly User Interface for Windows Operating System: A User Experience (UX) Driven Approach" which aims to improve the Windows user experience through better UI design. The main objective of this project is to explore and implement design principles that can improve the overall user experience. With a user experience (UX) based approach, this project identifies weaknesses in the current Windows interface, seeks innovative solutions, and tests their effectiveness through comprehensive user research. In this research, we produced several new features that were introduced including grouping, app drawer, and widgets, all of which are intended to ease navigation and improve efficiency of use.